2023
DOI: 10.1021/acssynbio.3c00114
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Expression System Derived from a Near-Minimal Synthetic Bacterium

Abstract: Cell-free expression (CFE) systems are fundamental to reconstituting metabolic pathways in vitro toward the construction of a synthetic cell. Although an Escherichia coli-based CFE system is well-established, simpler model organisms are necessary to understand the principles behind life-like behavior. Here, we report the successful creation of a CFE system derived from JCVI-syn3A (Syn3A), the minimal synthetic bacterium. Previously, high ribonuclease activity in Syn3A lysates impeded the establishment of func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Recent advancements in the quest for the minimal synthetic cell have been substantial, especially in critical areas such as physicochemical homeostasis, DNA replication, membrane growth, , and membrane scission. , The emerging synthetic cell will ultimately harness its own gene expression machinery to regulate these complex features. In vitro transcription-translation (in vitro transcription and translation (IVTT)) is a well-established technology for the synthesis of proteins from plasmids and linear DNA encoding for a small number of genes. Previous reports on phage genomes and large plasmids have shown that it is possible to express in the order of tens to a few hundred genes using DNA templates longer than 100 kbp. , Whereas these examples are excitingly close to a formerly postulated minimal genome (113 kbp with 151 genes), top-down experimental work on Mycoplasma established that the current minimal synthetic genome requires at least 493 genes. , From a bottom-up perspective, it is conceivable that the construction of synthetic cells requires similarly sized genomes, and these will need to be expressed in vitro. Presently, we do not know if there are limits to the size of template DNA that can be used in IVTT and whether IVTT will function efficiently from entire chromosomes that can be a thousand times larger than typically used plasmids .…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancements in the quest for the minimal synthetic cell have been substantial, especially in critical areas such as physicochemical homeostasis, DNA replication, membrane growth, , and membrane scission. , The emerging synthetic cell will ultimately harness its own gene expression machinery to regulate these complex features. In vitro transcription-translation (in vitro transcription and translation (IVTT)) is a well-established technology for the synthesis of proteins from plasmids and linear DNA encoding for a small number of genes. Previous reports on phage genomes and large plasmids have shown that it is possible to express in the order of tens to a few hundred genes using DNA templates longer than 100 kbp. , Whereas these examples are excitingly close to a formerly postulated minimal genome (113 kbp with 151 genes), top-down experimental work on Mycoplasma established that the current minimal synthetic genome requires at least 493 genes. , From a bottom-up perspective, it is conceivable that the construction of synthetic cells requires similarly sized genomes, and these will need to be expressed in vitro. Presently, we do not know if there are limits to the size of template DNA that can be used in IVTT and whether IVTT will function efficiently from entire chromosomes that can be a thousand times larger than typically used plasmids .…”
Section: Introductionmentioning
confidence: 99%
“…To optimize complex biological systems with minimal experimental effort, Pandi and coworkers recently reported a versatile workflow (METIS) that combines laboratory automation with active learning to explore the combinatorial space in iterative design-build-test cycles for (local) optima 15 . METIS successfully helped to improve several biological systems 3,[16][17][18] , including an in vitro CO2 fixation cycle of 27 different variables (CETCH cycle 2,19 ). The CETCH cycle converts CO2 into glycolate and could be improved by more than 10fold through METIS.…”
Section: Introductionmentioning
confidence: 99%
“…coli W3110 that did not affect the growth of the strain . The advantages of fewer metabolic pathways and interfering substances brought by gene deletion have made genome-reduced strain a promising choice for chassis cell of CFTT systems …”
Section: Introductionmentioning
confidence: 99%